Penerapan E-Procurement Mencegah Fraud Pada Pengadaan Barang Jasa Di Direktorat Samapta Polda Riau - Tampubolon, Dedy Aprianto; Purba, Rikardo (LPPM Universitas Putera Batam, 2024)
Manual procurement often triggers fraud, The purpose of this study is to determine and analyze the implementation of procurement of goods and services through electronic procurement. The method used is a qualitative method with data collection techniques through field observation, interviews and documentation studies. The subject of the study is the Directorate of Samapta Polda Riau. The results of this study prove that the implementation using an electronic procurement system has been running well and no fraud was found.